Sistem Pendukung Keputusan Pemilihan Jenis Lampu untuk Pencahayaan Ruangan Menggunakan Metode AHP - Zulkifli Zulkifli; Suwarti; Iwan Purnama; Nurhayati; Haris Tri Saputra (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Abstract is a brief summary of the paper to help readers quickly determine the main research problem, solutions to solving problems encountered, research objectives and temporary research results which can be in the form of numbers/percentages according to research needs. Abstract should be clear and informative, providing a statement for the problem under study and its solution. Abstract length between 90 to 230 words. Avoid unusual abbreviations and define all symbols used in the abstract. Using keywords related to the research topic is recommended